Minimizing cicatricial pemphigoid orodynia with minocycline. - Poskitt, L; Wojnarowska, F (1995)
Cicatricial pemphigoid is a rare autoimmune blistering disease of the elderly. It predominantly affects the mucosae, causing pain and scarring. the target antigen is within the lamina lucida of the basement membrane zone. Potential complications of systemic steroid and other immunosuppressive therapy have prompted trials of other means of treatment. We describe a series of seven patients treated with minocycline, six of whom derived sustained alleviation of orodynia. Four patients developed hyperpigmentation, and two complained of gastrointestinal discomfort which necessitated cessation of minocycline. Complete steroid withdrawal was achieved in two cases. Neither the disease progression nor the response to treatment was influenced by the immunoglobulin isotype or titre. The role of minocycline as a useful adjunct to therapy is discussed.